E-learning in Mongolian Higher Education - Tuul, Suvdmaa; Banzragch, Otgontugs; Saizmaa, Tsogzolmaa (International Review of Research in Open and Distributed Learning, 2016)
This paper reviews the e-learning course development in selected universities of Mongolia and attempts to classify the e-learning programs that are in practice at the tertiary education level in the country. The given paper uses both secondary and primary sources. The authors determined what factors influence e-learning type classification and how time consuming is e-learning in course development stage in comparison to that of face-to-face learning? Methods such as computation using threshold values, k-means clustering, and comparison of means using paired t tests were used. Furthermore, comparison of means was used to validate the factors. In conclusion, authors deliver recommendations based on analysis lessons learned for further development. This research has practical implications for higher education managers to make informed decisions.